Revisiting Glaziou and the botany of the second Cruls Mission: three new species and 23 accepted species of Myrcia (Myrtaceae) collected from Goiás, Brazil and a detailed description of his “Goyaz” itinerary - Rosa, Priscila O.; Vasconcelos, Thaís N.c.; Lucas, Eve J.; Proença, Carolyn E.b. (Phytotaxa, 2021)
Glaziou was one of the most prominent plant collectors in the history of Brazilian botany. His field expeditions during the second Cruls Mission (1894–1895) in the area now recognized as Goiás and Distrito Federal led him to collect 26 of the 32 species of Myrcia he was to name in his botanical career. Glaziou´s itinerary in the second Cruls Mission was reconstructed and mapped, showing he spent 40% of his collecting days in the present Distrito Federal and 60% in Goiás. His List of Species is now considered a suppressed work by the International Code of Nomenclature for the Algae, Fungi and Plants because he did not fulfill the criteria for formal species description. After examining over 300 specimens in Brazilian and European herbaria, we concluded that 23 of his names are synonyms of older, currently accepted names. The remaining three names are new species and are here formally described. This work underlines the importance of revisiting historical collections following recent changes in Myrcia taxonomy, to improve the understanding of species diversity in ecologically heterogeneous areas in large, morphologically complex genera such as Myrcia.